PENGARUH KEPEMILIKAN MANAJERIAL, KOMPENSASI BONUS, LEVERAGE, DAN PAJAK TERHADAP EARNING MANAGEMENT PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2014-2018 - Arif Efendi; M. Cholid Mawardi; Siti Aminah Anwar (Universitas Islam Malang, 2020)
This study aims to determine the Analysis of the Effect of Managerial Ownership Concentration, Binus Compensation, Leverage and Tax Against Earnings Management (Empirical Study of Manufacturing Companies Listing on the Indonesia Stock Exchange Period 2014 - 2018). The test using multiple linear regression models, as well as the number of samples in this study 49 samples in one study year can be obtained Simultaneously. The test results show that managerial ownership variables, Bonus Compensation, Leverage and Tax simultaneously have a significant effect on earnings management. Partial test results show that managerial ownership variables, Bonus Compensation and tax partially do not significantly influence earnings management. Whereas the Leverage variable partially affects the Earning Management. The results of this study are expected to provide input to company management in examining management behavior in earnings management practices and can contribute knowledge to future researchers.Keywords : managerial ownership, bonus compensation, leverage, tax and earnings management.